EFEKTIVITAS PERANCANGAN TYPEFACE DENGAN METODE IKONOGRAFI - Swaratama, Elfa; Achmad Zaki Yamani; Emmareta Fauziah (Institut Bisnis dan Teknologi Indonesia, 2020)
This article describes the typeface design method based on Dayak Iban tattoo. It uses iconographic theory from Erwin Panofsky and the evaluate it through a Likert survey on a scale of 1-5 using four aspects of assessment(similarity, uniqueness, readability, and legibility). Based on the iconographic analysis, this study categorizes Dayak tattoo motifs into three worlds, which are; The Upper World (Hornbill), Middle World (Tree of Life, Eggplant Flowers), and the Underworld (Dragon and Scorpion) will put on each letter anatomies. The evaluation stage found that the typeface has a 3.8 average level of uniqueness, readability, and legibility, although the level of similarity in this typeface with Dayak tattoo motifs needs to be increased again because of the score is just 3 of a maximum of 5.